Input Supply and Revenue Analysis of Seaweed Cultivation in Bungin Permai Village, Tinanggea Sub-district South Konawe District - Muh. Fais Slamet Alfahyed; Abdi, Abdi; Fahria Nadiryati Sadimantara (International Journal of Technology and Education Research, 2024)
This research was motivated by the input subsystem of the provision and distribution of seaweed seed production facilities and seaweed harvests, seaweed seed farmers generally produce their own seaweed seeds, some of which they will use for replanting and some will be sold in the form of seeds that are used by farmers to increase income. This research was conducted in Bungin Village, Tinanggea District, South Konawe Regency, Southeast Sulawesi. The purpose of this study was to determine how the supply of seaweed cultivation input subsystems in Bungin Permai Village, Tinanggea Subdistrict, South Konawe Regency and how much farmers' income from selling seaweed seeds in Bungin Permai Village, Tinanggea Subdistrict, South Konawe Regency. The population in this study were grass seed farmers in Bungin Permai Village with sampling using simple random sampling technique. This research uses qualitative descriptive analysis and income analysis using the income formula. The results of this study found that the supply of seaweed seeds in Bungin Permai Village, Tinanggea Subdistrict, South Konawe Regency is prepared by cultivating seaweed seeds and the harvest is stored in the yard of the seaweed farmer's house so that there are no storage costs to provide seeds for consumers. The average income of respondent farmers from the sale of seeds in seaweed farming in bungin permai village amounted to Rp1,964,624/ planting season